Career Options in the Pharmaceutical and Biomedical Industry An Insider's Guide - Thomas, Josse R.; Saso, Luciano; van Schravendijk, Chris (Cham : Springer International Publishing : Imprint: Springer, 2023)
Written by dedicated and active professionals from different areas of the pharmaceutical, biomedical, and medtech sectors, this book provides information on job and career opportunities in various life sciences industries. It also contains useful tips to launch your own startup. The pharmaceutical, biomedical and medical technology sectors offer a wide range of employment opportunities to talented and motivated young graduates. However, many of these employment prospects are not well known to early career scientists, who concentrate primarily on the scientific and academic content of their fields of interest. The book is divided into five parts: Part 1 provides an academic perspective that focuses on the specific preparation required in the final years of study to embark on a successful career in the pharmaceutical and biomedical industries. In Part 2, industry experts discuss employment possibilities all along the drug or product life cycle, from discovery research and development to commercialisation. Part 3 follows, highlighting opportunities in support functions such as regulatory affairs or quality assurance. Part 4 focuses on additional opportunities in the wider biomedical sector, while Part 5 contains practical tips and training opportunities for entering the pharmaceutical and biomedical industries. In the epilogue, the authors reflect on this fascinating field and its career prospects. The book offers a multidisciplinary perspective on career opportunities in the pharmaceutical and biomedical industry to a wide range of students and young life scientists. .
Part 1: Setting the scene -- Chapter 1: Life after Academia: Launching your Pharma/Biotech Career -- Chapter 2: Competences for Pharmacists -- Chapter 3: Job and Career Opportunities in the Pharmaceutical Industry: An Overview -- Part 2: Opportunities along the drug/product life cycle -- Chapter 4: Career Opportunities in Toxicology -- Chapter 5: Job Possibilities in Clinical Research -- Chapter 6: How to Get and Develop a Career in a Market Access Role in the Medical Devices Industry -- Chapter 7: Job Opportunities in Pharmaceutical Marketing -- Chapter 8: Working in Medical Affairs and Clinical Operations: Life-Changing Careers -- Chapter 9: The Role of Medical Science Liaison -- Chapter 10: Career Development for Physicians in the Biopharmaceutical Industry -- Part 3: Opportunities in Supportive Functions -- Chapter 11: Job and Career Opportunities in Regulatory Affairs/Science -- Chapter 12: Job Opportunities in Clinical Research Quality Assurance -- Chapter 13: Job Opportunities in Quality Assurance Related to Manufacturing of Medicinal Products -- Part 4: Other Opportunities in the Pharmaceutical and Biomedical Sector -- Chapter 14: Careers Perspective in a Science and Technology Park -- Chapter 15: To be or not to be: Entrepreneurship and Enterprise Creation as a Way to Innovate in Life Sciences -- Chapter 16: How to Become a Successful Hospital and Community Pharmacist -- Part 5: Practical tips and tricks -- Chapter 17: A Successful Career in the Life Sciences Industry: How to Write your Strongest Resumé and Ace that Interview -- Chapter 18: Skill Building for Career Advancement: Public Speaking and Networking -- Chapter 19: Training Opportunities for a Career in the Pharmaceutical and Biomedical Industry/Sector.
Keywords: Medicine -- Research; Biology -- Research; Vocational guidance; Career education; School management and organization; School administration; Biomedical Research; Career Counseling; Career Skills; Organization and Leadership